Vancomycin for dialytic therapy in critically ill patients: Analysis of its reduction and the factors associated with subtherapeutic concentrations - de Freitas, Fernanda Moreira [UNESP]; Zamoner, Welder [UNESP]; Dos Reis, Pamela Falbo [UNESP]; Balbi, André Luís [UNESP]; Ponce, Daniela [UNESP] (MDPI, 2020)
This study aimed to evaluate the reduction in vancomycin through intermittent haemodialysis (IHD) and prolonged haemodialysis (PHD) in acute kidney injury (AKI) patients with sepsis and to identify the variables associated with subtherapeutic concentrations. A prospective study was performed in patients admitted at an intensive care unit (ICU) of a Brazilian hospital. Blood samples were collected at the start of dialytic therapy, after 2 and 4 h of treatment and at the end of therapy to determine the serum concentration of vancomycin and thus perform pharmacokinetic evaluation and PK/PD modelling. Twenty-seven patients treated with IHD, 17 treated with PHD for 6 h and 11 treated with PHD for 10 h were included. The reduction in serum concentrations of vancomycin after 2 h of therapy was 26.65 ± 12.64% and at the end of dialysis was 45.78 ± 12.79%, higher in the 10-h PHD group, 57.70% (40, 48–64, 30%) (p = 0.037). The ratio of the area under the curve to minimal inhibitory concentration (AUC/MIC) at 24 h in the PHD group was significantly smaller than at 10 h (p = 0.047). In the logistic regression, PHD was a risk factor for an AUC/MIC ratio less than 400 (OR = 11.59, p = 0.033), while a higher serum concentration of vancomycin at T0 was a protective factor (OR = 0.791, p = 0.009). In conclusion, subtherapeutic concentrations of vancomycin in acute kidney injury (AKI) patients in dialysis were elevated and may be related to a higher risk of bacterial resistance and mortality, besides pointing out the necessity of additional doses of vancomycin during dialytic therapy, mainly in PHD.
Keywords: Acute kidney injury; Dialysis; Pharmacokinetic-pharmacodynamic; Sepsis; Vancomycin